2015
DOI: 10.1371/journal.pone.0134057
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Modulates Expression of the Airway Smooth Muscle Transcriptome in Fatal Asthma

Abstract: Globally, asthma is a chronic inflammatory respiratory disease affecting over 300 million people. Some asthma patients remain poorly controlled by conventional therapies and experience more life-threatening exacerbations. Vitamin D, as an adjunct therapy, may improve disease control in severe asthma patients since vitamin D enhances glucocorticoid responsiveness and mitigates airway smooth muscle (ASM) hyperplasia. We sought to characterize differences in transcriptome responsiveness to vitamin D between fatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Results highlight vitamin D-specific gene targets and provide novel transcriptomic data that can be used to further explore differences in ASM of patients with fatal asthma. 32 It is now well established that the inflammation in asthma involves several subsets of T-lymphocytes, not just Th2 cells. In naïve CD4 T-cells obtained from peripheral blood of young asthmatic subjects as well as healthy controls, it was found that stimulation of these cells under Th17 polarizing conditions led to the production of higher Th17 differentiation in asthmatic patients.…”
Section: Results From Human Studiesmentioning
confidence: 99%
“…Results highlight vitamin D-specific gene targets and provide novel transcriptomic data that can be used to further explore differences in ASM of patients with fatal asthma. 32 It is now well established that the inflammation in asthma involves several subsets of T-lymphocytes, not just Th2 cells. In naïve CD4 T-cells obtained from peripheral blood of young asthmatic subjects as well as healthy controls, it was found that stimulation of these cells under Th17 polarizing conditions led to the production of higher Th17 differentiation in asthmatic patients.…”
Section: Results From Human Studiesmentioning
confidence: 99%
“…248 Dissection of atopic disorders using these -omics approaches has been attempted at least to some extent. For example, transcriptome analyses have identified genes differentially expressed between asthmatic and control subjects 249 , between lesional and nonlesional skin in AD, 250 and between airway smooth muscles derived from patients with fatal asthma and healthy controls at baseline and after treatment with Vitamin D. 251 A recent study of transcriptome-wide responses to glucocorticoid treatment provides an interesting example of the use of transcriptomics to investigate the causes of population differences in allergic disease. 252 Proteomics has been used in several studies to identify biomarkers and peptide patterns associated with specific asthma endotypes.…”
Section: Omics-based System Biology Approach To Atopic Disordersmentioning
confidence: 99%
“…Analysis of the airway smooth muscle transcriptome in fatal and non-asthmatic derived ASM cells revealed that vitamin D induced differential expression of functional genes, such as those involved with the extracellular matrix and response to steroid hormone stimuli and wounding, as well as genes involved in cytokine and chemokine activity [65]. Using human fetal ASM cells as a model of the early post natal airways, it was found that calcitriol attenuated TNF-α enhancement of MMP-9 expression and activity as well as TNF-α and TGF-β induced collagen II expression and deposition [64].…”
Section: Vitamin D and Airway Smooth Muscle Cell Functionmentioning
confidence: 99%
“…Results highlight a potential role for vitamin D in the treatment of steroid-resistant asthma [68]. Treatment of ASM cells derived from fatal asthmatics with vitamin D inhibited TNF-α-induced IL-8 secretion from these cells when compared to non-asthmatic cells even though the fatal asthmatic ASM cells had significantly higher baseline levels of IL-8 [65]. …”
Section: Vitamin D and Airway Smooth Muscle Cell Functionmentioning
confidence: 99%